Comparative Anatomical Assessment of Full vs Limited Transcavernous Exposure of the Carotid-Oculomotor Window. Issue 1 (January 2022) - Cole, Tyler S.; Przybylowski, Colin J.; Houlihan, Lena Mary; Abramov, Irakliy; Loymak, Thanapong; Catapano, Joshua S.; Baranoski, Jacob F.; Srinivasan, Visish M.; Preul, Mark C.; Lawton, Michael T.
Abstract : BACKGROUND: Although the full transcavernous approach affords extensive mobilization of the oculomotor nerve (OMN) for exposure of the basilar apex and interpeduncular cistern region, this time-consuming procedure requires substantial dural dissection along the anterior middle cranial fossa. OBJECTIVE: To quantify the extent to which limited middle fossa dural elevation affects the carotid-oculomotor window (C-OMW) surgical area during transcavernous exposure after OMN mobilization. METHODS: Four cadaveric specimens were dissected bilaterally to study the C-OMW area afforded by the transcavernous exposure. Each specimen underwent full and limited transcavernous exposure and anterior clinoidectomy (1 procedure per side; 8 procedures). Limited exposure was defined as a dural elevation confined to the cavernous sinus. Full exposure included dural elevation over the gasserian ganglion, extending to the middle meningeal artery and lateral middle cranial fossa. RESULTS: The C-OMW area achieved with the limited transcavernous exposure, compared with full transcavernous exposure, provided significantly less total area with OMN mobilization (22 ± 6 mm 2 vs 52 ± 26 mm 2, P = .03) and a smaller relative increase in area after OMN mobilization (11 ± 5 mm 2 vs 36 ± 13 mm 2, P = .03). The increase after OMN mobilization in the C-OMW area after OMN mobilization was 136% ± 119% with a limited exposure vs 334% ± 216% with a full exposure. CONCLUSION: In this anatomical study, the full transcavernous exposure significantly improved OMN mobilization and C-OMW area compared with a limited transcavernous exposure. If a transcavernous exposure is pursued, the difference in the carotid-oculomotor operative corridor area achieved with a limited vs full exposure should be considered.